Key operational risk management techniques - Černohorská, Liběna; Rippel, Milan; Teplý, Petr (Univerzita Pardubice, 2010)
Operational risk has become one of the most discussed topics by both academics and practitioners in the financial industry in the recent years. The reasons for this attention can be attributed to higher investments in information systems and technology, the increasing wave of mergers and acquisitions, emergence of new financial instruments and the growth of electronic dealing. In addition, the New Basel Capital Accord (known as Basel II) demands a capital requirement for operational risk and further motivates financial institutions to more precisely measure and manage this type of risk. The aim of this paper is to shed light on main characteristics of operational risk management and common applied methods: scenario analysis, key risk indicators, risk control self assessment and loss distribution approach.
Keywords: operational risk; economic capital; Basel II; scenario analysis; key risk indicators; loss distribution approach